HUBUNGAN GAYA BELAJAR DENGAN PRESTASI AKADEMIK PADA SISWA DI SEKOLAH MENENGAH KEJURUAN (SMK) MUHAMMADIYAH 1 JAKARTA - Arif Budiman Amayase; Sri Maria Puji Lestari; Anggunan Anggunan; Octa Reni Setiawati (Jurnal Medika Malahayati, 2022)
Learning style is key to expanding performance in the work, at school and private situation. The learning style isdivided into three, namely visual learning style through what is seen, auditory learning style through what is heard and kinesthetic learning style through the movent and touch. Learning achievement is an assessment of the ability ofstudent after receiving the experience in a certain period of time that states in the form of latter, symbol or sentencesthat reflect the result that have been achieved by student. Knowing the relationship between the acedemic style with academic achievment in student at vocation high school (SMK) Muhammadiyah 1 Jakarta. Types of quantitative research, with an analytical design with a cross sectional approach. The sample used are students of SMK as many as 149 student. Data pickup using questionnaire style of assesment learning style and average report card value.Found that 149 respondent with result which is most of the learning style of kinesthetic as much as 54 student with a percentage and learning achievement is most obtained in the good category (83-91) as many as 89 student with apercentage of 59,7%. There is a difference between learning style and learning achievement in various student learning styles.